2010
DOI: 10.1159/000320455
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B among Pregnant Women and Its Impact on Pregnancy and Newborn Complications at a Tertiary Hospital in the Eastern Part of Germany

Abstract: Background and Aims: Prevalence data of hepatitis B virus (HBV) in pregnant women in the Eastern part of Germany are missing. More importantly, no data on HBV’s impact on pregnancy is known in patients living in the Western hemisphere. Our aim was to assess the prevalence of hepatitis B surface antigen (HBsAg) and its impact on pregnancy in women admitted to the department of gynecology at a German university hospital. Patients and Methods: 8,193 women who delivered at the university hospital between 2001 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
5
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 33 publications
(27 reference statements)
5
72
5
5
Order By: Relevance
“…Also, this prevalence varies from country to country, from one region to another region and from one group to another group in a country. [8][9][10] Prevalence of hepatitis B in pregnant woman worldwide is 1.5 to 2.5% whereas in India it varies from 0.2 to 7.7%. Prevalence of mean HBV carriers in India is 0.82% according to chatterjee et al 7 In our study prevalence rate is found to be 1.09% amongst indoor antenatal patients.…”
Section: Discussionmentioning
confidence: 99%
“…Also, this prevalence varies from country to country, from one region to another region and from one group to another group in a country. [8][9][10] Prevalence of hepatitis B in pregnant woman worldwide is 1.5 to 2.5% whereas in India it varies from 0.2 to 7.7%. Prevalence of mean HBV carriers in India is 0.82% according to chatterjee et al 7 In our study prevalence rate is found to be 1.09% amongst indoor antenatal patients.…”
Section: Discussionmentioning
confidence: 99%
“…But some of the other studies denied these effects and believed that there is a low risk of the transmission of hepatitis B through the placenta, indicating these pregnancies are the same as non-infected pregnancies (17,23,28,31).…”
Section: Discussionmentioning
confidence: 99%
“…For quality assessment, we used the modified version of STROBE (17) which includes seven items of STROBE checklist (setting, participation, variables, bias, limitation and interpretation).There were eight low-risk studies and ten high-risk studies (5,(17)(18)(19)(20)(21)(22)(23)(24)(25) among the included studies (Figure 1). …”
Section: Methodological Quality Assessment Of the Included Studiesmentioning
confidence: 99%
“…Although some studies suggest that there may be an increase in the complications of pregnancy, such as gestational diabetes, antepartum hemorrhage, and preterm labor in CHB mothers (Tse et al 2005), this has not been supported by other large-scale studies Lobstein et al 2011).…”
Section: Effects Of Pregnancy On Hepatitis B Carrier Mothersmentioning
confidence: 92%